Development of PVDF/PEG Thin Film Composite Membrane For CO2/N2 Gas Separation - Nurfariha, Kamaruddin (2013)
PVDF/PEG) thin film composite (TFC) membrane for CO2/N2 gas separation. Asymmetric thin flat sheet membrane was prepared by dry wet phase inversion process consisting 15 %w/v of (PVDF) as the support layer polymer, 82 %w/v of N-methyl-2- pyrrolidone (NMP) as the solvent and 3 %w/v of distilled water as the non-solvent. Different concentration of poly (ethylene glycol) (PEG) polymer acts as the top film was study with 10 %, 15%, and 20% by using dip-coating method. The morphological structures of produced membranes were examined using Scanning Electron Microscopy (SEM). The Fourier Infrared Spectroscopy (FTIR) analysis also conducted in order to characterize the existence of the chemical bonding type in the membrane. The performance of the membrane was examined by conducting the gas permeation test. Pure carbon Dioxide (CO2) and pure nitrogen (N2) were used as the test gases by using feed ration range from 0.5 to 1.5 bars. As expected by the morphological structure, 10% PVDF/PEG (TFC) membrane showed the best performance compared to 15% and 20% PVDF/PEG TFC membrane. The selectivity of CO2/N2 was (1.01 at 0.5 bar), (1.07 at 1.0 bar) and (1.08 at 1.5 bar) for 20% PVDF/PEG TFC membrane, (1.02 at 0.5 bar), (1.11 at 1.0 bar) and (1.22 at 1.5 bar) for 15% PVDF/PEG TFC membrane, (1.03 at 0.5 bar), (1.27 at 1.0 bar), (1.43 at 1.5 bar) for 10% PVDF/PEG TFC membrane. From the investigation, PVDF/PEG (TFC) membrane was pointed the higher performance of selectivity and permeability behavior and hereby supposedly selected for future membrane development. The concentration of top layer membrane was discovered to affect the morphological structure which will preferentially affect the performance of the PVDF/PEG TFC membrane. Therefore, from the study conducted the most suitable asymmetric (TFC) membrane to developed high performance with concentration in range of 10% PVDF/PEG TFC membrane.